Viability of Lactobacillus plantarum TISTR 2083 in protectant during low-temperature drying and storage - Abdullah Al Mamun; Payap Masniyom; Jaruwan Maneesri (Penerbit Universiti Kebangsaan Malaysia, 2021)
Low-temperature drying was applied as simple and low cost drying technique for the production of dried Lactobacillus plantarum TISTR 2083, which was isolated from traditional starter of Ka-nom Tuay-fu. To improve the survival of L. plantarum TISTR 2083 during drying and storage, five different protectants and two carrier materials were investigated. These include sucrose, trehalose, maltodextrin, skim milk, and L-glutamate sodium salt (L-GSS) as protectant and rice starch and rice flour as carrier material. Whereas, skim milk as protectant with rice starch resulted in higher viable cell (8.71 log CFU/g) after drying by hot air oven at 40 °C. Different concentration 5, 10, and 15% (w/v) skim milk also investigated to check the effect of skim milk concentration on cell viability. L. plantarum TISTR 2083 starter powder was in different storage conditions to check the storage stability. After 90 days of storage, starter powder stored at 4 °C with silica gel and without silica gel had more than 80% survival rate, while there was no viable cell that stored in room temperature with silica gel. The result showed the production and storage conditions of high viability L. plantarum TISTR 2083, which can be used as starter culture for further fermented product development and as probiotic.